Comparison between Double Stranded DNA with Restriction Enzymes and Single Stranded DNA with Primers for Solving Boolean Matrix Multiplication - Nordiana, Rajaee; Awang Ahmad Sallehin, Awang Husaini; Azham, Zulkharnain (UTEM, 2017)
Boolean matrix multiplication is the basis for most computing algorithms and is widely used in many fields. In this paper, we compare and discuss two methods to solve Boolean matrix multiplication with DNA computing. The first method utilizes double stranded DNA sequences with Restriction Enzymes meanwhile the second method utilizes single stranded DNA sequences with primers. We prove that while both methods are able to solve the Boolean matrix multiplication problem, these two methods differ in their performance and output results. We compare the advantages of the latter method in terms of easier sequence designs and more efficient analysis of results.